On the stream-dwelling Crossodactylus timbuhy (Anura, Hylodidae): taxonomy, natural history, and geographic distribution - Lacerda, João Victor A.; Montesinos, Rachel; Zocca, Cássio; Guimarães, Carla S.; Santana, Diego J.; Ferreira, Rodrigo B. (Zootaxa, 2022)
The genus Crossodactylus has taxonomic problems due to the difficulty in properly identifying some populations to the species level. The deficient species diagnosis rises mostly due to high intraspecific variation and lack of information on topotypes. Crossodactylus timbuhy was described based only on external morphology of preserved adult specimens. Based on topotypic specimens, we provide further information on C. timbuhy regarding color in life (both adult and larvae), tadpole external morphology, vocal repertoire, natural history, and geographic distribution. The species identification was confirmed through comparison to the type series, 16S rRNA analysis, and bioacoustics. Crossodactylus timbuhy vocalizes during daylight along shallow slow-flowing streams. The advertisement call has ascendant amplitude modulation, duration of 2.1–8.4 s, 23–75 pulsed notes, and peak frequency of 3.6–4.8 kHz. Our report on male unilateral sac inflation is the first within Crossodactylus. Although overall tadpole external morphology and coloration resemble other species of hylodids, we report ventral depression and golden iridophores also for the first time within Crossodactylus. Adult males display five antipredator mechanisms (interrupt calling, escape, aggression, posture, and aposematism). Finally, we restrict its geographic distribution to the Municipality of Santa Teresa, State of Espírito Santo, Southeastern Brazil.